Universal Electroluminescence at Voltages below the Energy Gap in Organic Light‐Emitting Diodes. Issue 21 (19th August 2021) - Li, Yungui; Sachnik, Oskar; van der Zee, Bas; Thakur, Kalyani; Ramanan, Charusheela; Wetzelaer, Gert‐Jan A. H.; Blom, Paul W. M.
Abstract: In organic light‐emitting diodes (OLEDs), it is typically assumed that a voltage equal to or higher than the energy gap of the emitters is required to observe electroluminescence (EL). However, EL at subgap voltages is observed and proposed to originate from up‐conversion processes, such as fusion of low‐energy triplet excitons. Here, it is demonstrated that EL at subgap voltages in OLEDs is universally present. By using emitters with negligible energy splitting between the singlet and triplet state, the need for incorporating low‐energy triplet excitons is ruled out. The origin of EL at voltages below the energy gap is the recombination of diffused and thermally generated charge carriers, universally present in light‐emitting diodes at nonzero temperatures, theoretically permitting electrical‐to‐optical power‐conversion efficiencies exceeding unity. Abstract : Electroluminescence (EL) at subgap voltages is universally present in organic light‐emitting diodes (OLEDs), stemming from the recombination of diffused and thermally generated charge carriers at nonzero temperatures. Without the need of energy up‐conversion processes, the EL at subgap voltages from OLEDs makes electrical‐to‐optical power‐conversion efficiencies exceeding unity theoretically possible.